GRB060206 and the quandary of achromatic breaks in afterglow light curves - Curran, Peter; van der Horst, A.; Wijers, R.; Starling, R.; Castro-Tirado, A.; Fynbo, J.; Gorosabel, J.; Jarvinen, A.; Malesani, D.; Rol, E.; Tanvir, N.; Wiersema, K.; et al. (Oxford University Press, 2007)
Gamma-ray burst afterglow observations in the Swift era have a perceived lack of achromatic jet breaks compared with the BeppoSAX era. We present our multi-wavelength analysis of GRB060206 as an illustrative example of how inferences of jet breaks from optical and X-ray data might differ. The results of temporal and spectral analyses are compared, and attempts are made to fit the data within the context of the standard blast wave model. We find that while the break appears more pronounced in the optical and evidence for it from the X-ray alone is weak, the data are actually consistent with an achromatic break at about 16 h. This break and the light curves fit standard blast wave models, either as a jet break or as an injection break. As the pre-Swift sample of afterglows are dominated by optical observations, and in the Swift era most well-sampled light curves are in the X-ray, caution is needed when making a direct comparison between the two samples, and when making definite statements on the absence of achromatic breaks.